Personifikasi dan Simile dalam Prosa Lirik Pengakuan PARIYEM KARYA Linus Suryadi A.G. - Mujid Farihul Amin; Ary Setyadi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
This research is aimed to know the function of personification and simile in lyrical prose Pengakuan Pariyem. The method used in this research is the common method used in stylistics. Conclusion: personification indicates that it function is to describe real and living atmosphere, enabling to create both image and aesthetic of the speech. Simile, does not only indicate its function as aesthetic maker, but also to create image itself contextually.